1999
DOI: 10.1017/s000711459900015x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sodium fumarate addition on rumen fermentationin vitro

Abstract: The influence of sodium fumarate on rumen fermentation was investigated in vitro using batch and semi-continuous cultures of mixed rumen micro-organisms taken from three sheep receiving a basal diet of hay, barley, molasses, fish meal and a mineral–vitamin supplement (500, 299·5, 100, 91 and 9·5 g/kg DM respectively). Batch cultures consisted of 10 ml strained rumen fluid in 40 ml anaerobic buffer containing 200 mg of the same feed given to the sheep. Sodium fumarate was added to achieve a final concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
73
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 25 publications
20
73
1
2
Order By: Relevance
“…In the Rusitec, 6.25 mmol fumarate caused a 1.2 mmol fall in methane production (Lopez et al 1999). In our in vivo study (Yuan et al 2007), daily methane production was reduced by 9.6% on addition of TSDF, but if only DF was used, almost 2 mol (more than 300 g) of DF was needed to achieve the same level of methane reduction.…”
Section: The Interaction Between Tea Saponins and H 2 Acceptormentioning
confidence: 52%
“…In the Rusitec, 6.25 mmol fumarate caused a 1.2 mmol fall in methane production (Lopez et al 1999). In our in vivo study (Yuan et al 2007), daily methane production was reduced by 9.6% on addition of TSDF, but if only DF was used, almost 2 mol (more than 300 g) of DF was needed to achieve the same level of methane reduction.…”
Section: The Interaction Between Tea Saponins and H 2 Acceptormentioning
confidence: 52%
“…Nitrate decreases methane production by acting as a hydrogen sink and inhibiting the growth and activities of methanogens through the intermediate products of nitrate metabolism by nitrate reducing bacteria (Leng, 2008;Patra and Yu, 2013). Organic acids that are intermediates of propionate production such as malate and fumarate enhance propionate concentration with a stoichiometric decrease in hydrogen availability for methane synthesis (Lopez et al, 1999;Ungerfeld and Kohn, 2006). Based on these backgrounds, it was hypothesized that incorporation of tree leaves along with nitrate or fumarate may additively lower methane production in the rumen.…”
mentioning
confidence: 99%
“…Hence, less methane production (Martin 1998;Lopez et al 1999a) was reported. Addition of sodium fumarate in vitro decreased methane production and also increased dry matter digestibility (Lopez et al 1999b). Asanuma et al (1999) found that fumarate also reduced methane production in vitro and suggested it to be an economical feed additive.…”
Section: Propionate Enhancersmentioning
confidence: 99%